CAN WHITE AMERICANS INCLUDE COLORS IN THEIR CANON? SEARCHING A POST-NATIONAL HISTORY OF AMERICAN PHILOSOPHY - Ferry Hidayat (Universitas Gadjah Mada, 2022)
Racism in the USA not only takes place in law, economics, politics, mass media and new media, education, literature, and popular culture but also occurs in philosophy. An abundance of Latino philosophers, African-American philosophers, and Native American philosophers are excluded from the American philosophy canon. To discover whether racism happens in the field of American philosophy, the writer surveys 15 American philosophy books written between the 1940s and the 2020s by various American writers, the whites and the non-whites. The writer carries out an ‘index-study’: scanning philosopher names in the index of each book, identifying and scrutinizing the names, listing and categorizing them into race categories, counting them, comparing the number of non-white philosophers and white philosophers mentioned in each book, putting them in a table, and interpreting why there is a disparity between the number of non-white and white philosophers included in the books. The survey result shows that racism happens in American philosophy; the writers of the 15 American philosophy books exclude an abundance of non-white philosophers. There is a critical need to write a new, post-national American philosophy book that does justice to non-white philosophers in the near future so that racism diminishes.